Isolated Medial Patellofemoral Ligament Reconstruction Under Increased Femoral Anteversion Is Associated With Increased Contact Pressure of Medial Patellofemoral Facet at Deep Flexion Angle: A Cadaveric Study - Park, Jisu; Piao, Zhanguang; Shin, Seonjin; Kim, Tae Woo; Chang, Moon Jong; D’Lima, Darryl D.; Kwak, Dai-Soon (Arthroscopy, 2025)
To analyze (1) whether isolated medial patellofemoral ligament (MPFL) reconstruction in increased femoral anteversion could replicate the patellofemoral (PF) pressure pattern of a hypothetical normal population and (2) the change of PF pressure according to MPFL state under the same anteversion setting. Ten fresh-frozen cadaveric knees were used. Experiments were performed from knee flexion 0° to 90° with 3 MPFL state (intact, released, and reconstructed) and 3 anteversion (initial state, 10° and 20° more increased). Medial and lateral PF joint contact pressures were measured at each point. At 0° flexion, lateral PF pressure was increased to 62.1 ± 7.8 psi in 10° and 67.3 ± 13.5 psi in 20° more increased anteversion, compared with 43.2 ± 8.6 psi of hypothetical normal population (P .027 and .004, respectively). At 30° flexion, medial PF pressure was decreased to 31.3 ± 11.9 psi in 10° and 27.3 ± 17.5 psi in 20° more increased anteversion, compared with 44.1 ± 10.3 psi of hypothetical normal population (P .009 and .027, respectively). Within the same femoral anteversion, when anteversion was increased 10° and 20° more than the initial state, medial facet pressure after MPFL reconstruction at 90° flexion was increased from 28.7 ± 11.4 psi to 40.0 ± 9.9 psi and 16.7 ± 10.8 psi to 33.9 ± 15.0 psi compared with the intact MPFL (P .047 and <.001, respectively). Biomechanically, isolated MPFL reconstruction under increased femoral anteversion was unable to replicate the state of a hypothetical normal population. Even when comparing within the same femoral anteversion, isolated MPFL reconstruction at increased femoral anteversion caused medial PF overpressure at 90° flexion angle. When performing MPFL reconstruction for recurrent patellar dislocation, femoral anteversion should be assessed. Increased femoral anteversion can cause overpressure on the medial facet after isolated MPFL reconstruction.